Gestão estratégica da informação em coordenações de cursos de graduação: proposta para Engenharia de Produção - Camboim, Luzia Góes (2017)
This is an empirical study on the theme Strategic Information Management with the general purpose of develop a Strategic Information Management model appropriate to the course coordination degree in Production Engineering of federal public universities, especially in the case of Pernambuco Federal University. The intention is to propitiate the globally improvement of the results, achieved by coordination of undergraduate courses, compared to the current requirement standards in line with global tendencies for the management activity, including for the public sector. These are the specific objectives: (i) identify allusive documentation to the strategies outlined for undergraduate courses of Production Engineering of UFPE; (ii) map the formal information flows that pervade the scope of the course coordination, whether internal or external source, whether in situational or permanent perspective; (iii) describe the steps of the Strategic Information Management used in the course of coordination in the decision-making process in situational perspective; (iv) confront the form of management of information flows identified with the models available in the literature on the subject in the context of Information Science; (v) identify, in the empirical reality studied, the points where there are obstacles to the decision-making process as well as its causes, from the point of view of the management of information flows; (vi) propose the necessary adjustments, based on the literature review undertaken for adhesion between the management of the mapped information and Strategic Information Management in the undergraduate course coordination. The relevance of the work is justified because universities are institutions indispensable to any nation's development process. Among the technology-based courses with significant demand in Brazil, Production Engineering stand out because of their skills strongly related to industrial plans for innovation and effective management as a way to consolidate and increase the degree of competitiveness of the domestic industry. By having a qualitative profile, this research was conducted as a case study over the course of a federal university in the Northeast (Federal University of Pernambuco). Resorting to questionnaire (students) and interview techniques for the academic community (administrators), whose contents was analyzed by the Content Analysis method (AC), with the addendum that the sample (for the academic students) resulted from the application of stratified random sampling technique. It was observed that the Strategic Management of Information on the studied IFES, although presenting systematization, this management activity does not come from prior planning, characterized by empiricism and, not necessarily, respecting a formal information flow. There is not a total adherence between the literature on the Strategic Management of Information and what is executed in this coordination, but from some adaptations they can have a model that target better such activity. With this, it was proposed a model based on current models of information management, which takes into account also the definition of a strategic objective aimed, as a starting point, and a selection of strategic documents of interest, before the stage of informational needs identification. In addition, it is suggested a stage of selection/adaptation/ development of appropriate IT to the informational collection and processing of information, besides a stage of adaptive behavior without which the phase of use of information can be impaired.